2020
DOI: 10.1080/09638288.2020.1793008
|View full text |Cite
|
Sign up to set email alerts
|

The physical environment and multi-professional teamwork in three newly built stroke units

Abstract: Purpose: To explore multi-professional teamwork in relation to the physical environment in three newly built or renovated stroke units. Materials and methods: An observational study was undertaken. The participants were all staff members of a multi-professional team working in the reviewed stroke units. The data were collected using behavioural mapping and semi-structured observations, and they were analysed by content analysis and descriptive statistics. Results: Out of all the observations in the behavioural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…31 An observational study of multiprofessional teamwork in three stroke units found that the design of the included stroke units did not appear to foster multiprofessional teamwork: Centrally located staff workplaces, such as the nurses' stations, created visible hubs but were not appropriate for confidential discussions between staff; none of the stroke units had dedicated rooms for multiprofessional meetings; and each profession worked mainly in their own dedicated offices. 48 The qualitative meta-synthesis conducted by O'Halloran et al 46 addressed the question of patient/staff communication and concluded that high levels of background noise, visual distractions and a lack of single-bed rooms acted as environmental barriers to communication between patients and staff. In another qualitative study, occupational therapists reported adapting their treatment sessions according to the available space, indicating that the suitability of therapy spaces impacts treatment decision-making.…”
Section: Open Accessmentioning
confidence: 99%
“…31 An observational study of multiprofessional teamwork in three stroke units found that the design of the included stroke units did not appear to foster multiprofessional teamwork: Centrally located staff workplaces, such as the nurses' stations, created visible hubs but were not appropriate for confidential discussions between staff; none of the stroke units had dedicated rooms for multiprofessional meetings; and each profession worked mainly in their own dedicated offices. 48 The qualitative meta-synthesis conducted by O'Halloran et al 46 addressed the question of patient/staff communication and concluded that high levels of background noise, visual distractions and a lack of single-bed rooms acted as environmental barriers to communication between patients and staff. In another qualitative study, occupational therapists reported adapting their treatment sessions according to the available space, indicating that the suitability of therapy spaces impacts treatment decision-making.…”
Section: Open Accessmentioning
confidence: 99%
“…11 Shared staff spaces support team communication and collaboration, enabling better understanding of patient needs, and greater knowledge about other team roles. 58,59 Therapy spaces are often discrete locations (e.g. gym, occupational therapy rooms), rather than being holistic, context-based environments that reflect the connectivity and continuity necessary for rehabilitation and transition beyond discharge.…”
Section: Efficiency Of Care Staff Processes and Communicationmentioning
confidence: 99%